MOTIF DIPLOMASI PERTAHANAN INDONESIA DENGAN CINA DALAM MENYELESAIKAN KONFLIK PERAIRAN NATUNA UTARA TAHUN 2019 - Debora, Rizpani; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesia objected to the unilateral claim of the Natuna waters map made by the Chinese government. The map shows nine dots nine dash line which determines the boundaries of the territory that is part of China's territory over parts of the Natuna Waters. The overlapping claims referred to by China are areas referred to as traditional fishing grounds which are not recognized in the international law of the sea UNCLOS (United Nations Convention on the Law of the Sea). This has become a guideline for China to continue committing illegal fishing in Indonesia's sovereign territory. Indonesia must face this potential conflict considering that China stated that part of the North Natuna Waters is its territory. This research uses the theory of Indonesian defense diplomacy, influenced by a realism perspective where Indonesia has an interest in fighting for and defending its national interests anticipating conflicts in the North Natuna Waters, as well as maintaining Indonesia's maritime stability and sovereignty. Forms and efforts to resolve illegal fishing are carried out by increasing security in the North Natuna Waters by the Indonesian Navy with the support of the government and the relevant agencies. Indonesia's strategy in maintaining defense diplomacy peacefully is motivated by the cooperation between Indonesia and China been doing for a long time. Both countries strengthen cooperation in several strategic sectors such as trade, finance, infrastructure, industry, tourism, to politics and security. In the era of President Joko Widodo's administration, economic cooperation between Indonesia and China was also very dynamic in various fields. So that this relationship is the reason for Indonesia to continue to maintain peaceful diplomacy. Keywords: North Natuna Waters, Unilateral Claim, National Interest, Defense Diplomacy.